Analysis of Ways to Increase the Effectiveness of Active Marketing in Food Industry Enterprises - Boyquzieva Gulsanam Adxamovna (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
Marketing analysis of competitors' activities, and searching for forms of cooperation with them will help not only, but also the education of a highly cultured, harmonious, highly ethical consumer. Success in this field is achieved through the high professional skills of marketers who understand the wishes of consumers, can accurately predict the dialectic of demand and its aspects, know the possibilities of the field of activity, and can ensure the dynamism, flexibility and elasticity of the system. This article analyses the ways, mechanisms and theoretical foundations of improving the efficiency of management of food industry enterprises, and gives conclusions and recommendations.